Barriers and facilitators to participate in behavior change program: analysis of focus groups Barreiras e facilitadores para a participação em um programa de mudança de comportamento: análise de grupos focais - Tonosaki L.M.D. (2018)
© 2018 Colégio Brasileiro de Ciências do EsporteThis study was aimed to examine barriers and facilitators to participate in a behavior change program participants in Primare Care Health. Content analysis was used to evaluate four focus groups attended by 35 people (≥ 18 years), of both sexes, different Health Centers in Florianopolis. Lack of classroom practice, climatic variations, physical limitations, sheet of materials, lack of security/structure and shyness were cited as barriers. On the other hand, good quality of materials, quality multiplier, pedometer distribution, improved body awareness, goal setting and social support were reported as facilitators. It has been found that there are barriers and facilitators should be considered in the new program versions.